2019
DOI: 10.1038/s41419-019-1600-7
|View full text |Cite
|
Sign up to set email alerts
|

TFAP2B overexpression contributes to tumor growth and progression of thyroid cancer through the COX-2 signaling pathway

Abstract: Thyroid cancer is commonly seen in the clinic with a rapidly increasing incidence globally. COX-2 overexpression correlates with the pathologic type of thyroid carcinoma, and it has been suggested that COX-2 overexpression is associated with a poor prognosis. However, little is known about its upstream regulatory mechanism. Bioinformatics suggested that transcription factor AP-2 beta (TFAP2B) might specifically bind to the COX-2 promoter, which was confirmed by biotin-labeled COX-2 promoter pulldown and lucife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…It is essential to detect novel valid therapeutic target for papillary thyroid cancer mainly for cases resistant to currently used therapies. In our study, we found that TFAP2B expression was elevated in cells of papillary thyroid cancer in comparison to adjacent non-neoplastic thyroid tissues which are similar to results of Fu et al, (2019), in papillary thyroid cancer and Fu et al, (2014) in lung cancer. Fu et al, (2019) showed that TFAP2B expression in lung cancer tumor tissue samples is markedly elevated in comparison to healthy tissues.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…It is essential to detect novel valid therapeutic target for papillary thyroid cancer mainly for cases resistant to currently used therapies. In our study, we found that TFAP2B expression was elevated in cells of papillary thyroid cancer in comparison to adjacent non-neoplastic thyroid tissues which are similar to results of Fu et al, (2019), in papillary thyroid cancer and Fu et al, (2014) in lung cancer. Fu et al, (2019) showed that TFAP2B expression in lung cancer tumor tissue samples is markedly elevated in comparison to healthy tissues.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, Fu et al, (2019), stated that knocking down TFAP2B in cell lines of thyroid cancer reduced viability, proliferation, migration, and invasion of cancer cells. In our study, we clarified that TFAP2B higher expression increased the growth of papillary thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This gene has been shown to harbor aberrant methylation in primary breast tumors [25]. The TFAP2B gene codes for the transcription factor AP-2 beta, a sequence-specific DNA-binding protein that has been recognized as an oncogene that mediates cancer cell proliferation, apoptosis, invasion, and migration via the COX-2 signaling pathway in vitro and in vivo [26]. TFAP2B is also expressed in breast tissue, where it is thought to coordinate HER2 and ER [27] and has been associated with breast cancer prognosis [28].…”
Section: Discussionmentioning
confidence: 99%